2011
DOI: 10.1055/s-0031-1275706
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation in Macrophage Migration Inhibitory Factor Associated with Gestational Diabetes Mellitus and Metabolic Syndrome

Abstract: The aim of this study was to investigate the association of macrophage migration inhibitory factor (MIF) polymorphism rs1007888 with gestational diabetes mellitus (GDM), and its association with postpartum metabolic syndrome. In a case-control study, 147 GDM and 169 healthy pregnant patients were recruited. Blood sample was taken 2 times from all the participants; one at 24-28 weeks of gestation, second at 6-12 weeks of postpartum. Biochemical measurement and DNA extraction were performed. The PCR_SSP was perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…Certain roles in macrophage accumulation and inflammatory reactions could be attributed to the proinflammatory cytokine called macrophage migration inhibitory factor, which has pleiotropic immune functions (Nishihira 2000). Migration inhibitory factor concentrations are increased in GDM and its polymorphisms associate with susceptibility to GDM development in pregnancy (Aslani et al 2011, Yilmaz et al 2012. Apart from proinflammatory cytokine production, M1 macrophages represent the potential source of reactive oxide species and nitric oxide (Mantovani et al 2004) that may eventually contribute to the development of adipose tissue (Jang et al 2016) and placental fibrosis Krzyzanowska et al 2006, Lewandowski et al 2007(Chan et al 2006, Haider et al 2007 ↑ (Chang et al 2011) -…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Certain roles in macrophage accumulation and inflammatory reactions could be attributed to the proinflammatory cytokine called macrophage migration inhibitory factor, which has pleiotropic immune functions (Nishihira 2000). Migration inhibitory factor concentrations are increased in GDM and its polymorphisms associate with susceptibility to GDM development in pregnancy (Aslani et al 2011, Yilmaz et al 2012. Apart from proinflammatory cytokine production, M1 macrophages represent the potential source of reactive oxide species and nitric oxide (Mantovani et al 2004) that may eventually contribute to the development of adipose tissue (Jang et al 2016) and placental fibrosis Krzyzanowska et al 2006, Lewandowski et al 2007(Chan et al 2006, Haider et al 2007 ↑ (Chang et al 2011) -…”
Section: Journal Of Endocrinologymentioning
confidence: 99%
“…Furthermore, associations between MIF genotype Rs1007888GG and gestational diabetes as well as pre-pregnancy obesity and family history of diabetes have been reported (55). This specific genotype was also found to be twofold more frequent in women with metabolic syndrome (55). …”
Section: Human Studiesmentioning
confidence: 99%
“…The PCR amplification primers were designed based on relevant literature (Aslani et al, 2011) and the original DNA sequence reported in GenBank. Primer synthesis was performed by Shanghai Sunny Biotechnology Co., Ltd. (Shanghai, China).…”
Section: Detection Of Mif Rs1007888 Polymorphismmentioning
confidence: 99%
“…Macrophage migration inhibitory factor (MIF) is a protein that can function as a cytokine, hormone, or enzyme and exhibits a variety of biological activities, playing an important role in inflammation and immunity (Grieb et al, 2010). Previous studies have shown that MIF is related to the occurrence of obesity and insulin resistance syndromes (Finucane et al, 2012), and MIF gene polymorphisms have been correlated with GDM and metabolic syndromes (Aslani et al, 2011). To further validate the genetic susceptibility to GDM based on MIF gene polymorphisms, we used polymerase chain reaction (PCR) and DNA direct sequencing technology to analyze the MIF rs1007888 locus.…”
Section: Introductionmentioning
confidence: 99%